Odgovori na pitanja o pitanjima - Badurina, Lada (Slavistična revija, 2018)
In this article, questions are treated as a pragmatic category-that is, as a category closely related to the speech act (i.e., to the speaker and his interlocutor), and are in this sense distinguished from interrogative sentences, which are a syntactic (grammatical) category. Based on this distinction, the article establishes that the formal grammatical structure (interrogative sentence) and question as a type of speech act are not necessarily the same thing. For example, there are questions the structure of which is the same as that of declarative sentences, differing from statements only in the intonation used (e.g., Name? Or Coming?), and there are those which, despite the fact that they have the structure of an interrogative sentence, do not require the interlocutor to respond but instead to react in some way (Why is the window closed?, Are you trying to pick a fight? or Oughtn't you apologize?). In the remainder of the article, questions are analyzed through the prism of interlocutors' interaction, with special attention devoted to the potential illocutionary force of questions.
Keywords: govorno dejanje; hrvaščina; ilokucija; jezikoslovje; vprašanja